2022
DOI: 10.1038/s41598-022-13594-3
|View full text |Cite
|
Sign up to set email alerts
|

A miRNAs catalogue from third-stage larvae and extracellular vesicles of Anisakis pegreffii provides new clues for host-parasite interplay

Abstract: Anisakids are widespread marine parasites of medical, veterinary and economic relevance. They infect marine natural hosts but humans can accidentally acquire the fish-borne zoonosis anisakiasis by ingesting infected raw fishes or mollusks. Among the several species described, Anisakis pegreffii is one of the main etiological agent of the disease, in particular in the Mediterranean area. Despite the growing evidence of miRNAs involvement in host-parasite interplay, and the emerging role of exosomal microvesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…So far, the proteomic profiling of ESPs has been described for the species A. simplex (s.s.) ( Kochanowski et al., 2022 ), while no specific analysis is available for ESPs of A. pegreffii . Recently, EVs from the A. pegreffii L3 were shown to deliver miRNA ( Cavallero et al., 2022a ), while the proteomic information available for L3-EVs are referred to Anisakis sp. ( Boysen et al., 2020 ), although the object of that study was likely the species A. simplex (s.s.) being the larvae collected from Clupea harengus of the NE Atlantic Ocean, which has been found parasitised by that species ( Mattiucci et al., 2018b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the proteomic profiling of ESPs has been described for the species A. simplex (s.s.) ( Kochanowski et al., 2022 ), while no specific analysis is available for ESPs of A. pegreffii . Recently, EVs from the A. pegreffii L3 were shown to deliver miRNA ( Cavallero et al., 2022a ), while the proteomic information available for L3-EVs are referred to Anisakis sp. ( Boysen et al., 2020 ), although the object of that study was likely the species A. simplex (s.s.) being the larvae collected from Clupea harengus of the NE Atlantic Ocean, which has been found parasitised by that species ( Mattiucci et al., 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the proteomic composition of EVs have been reported in Anisakis spp. ( Boysen et al., 2020 ), while miRNAs have been studied and recorded in A. pegreffii ( Cavallero et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress using omic methodologies have provided new information on the virulence and pathogenic repertoire of fish zoonotic parasites. It has been demonstrated that the L3 of A. pegreffii secrete these factors, either as free proteins in the secretome (Trumbić et al., 2021 ), or packaged in form of extracellular vesicles (EVs) (Boysen et al., 2020 ;Cavallero et al., 2022 ; Palomba, Rughetti, et al., 2023 ). These products have a role in the larval invasion mechanism and the immunomodulation of the host's response, in particular the evasion from the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…These products have a role in the larval invasion mechanism and the immunomodulation of the host's response, in particular the evasion from the immune system. It has been suggested that the pathogenicity of A. pegreffii L3 is likely the result of the direct invasive capability of the larva, its released excretory secretory products (ESPs) (Trumbić et al., 2021 ), including those transported by EVs (Cavallero et al., 2022 ; Palomba, Rughetti, et al., 2023 ), as well as the intricate interplay of the host's immune response (Mehrdana et al., 2017 ). Among ESPs an array of peptidases and peptidase inhibitors are considered essential for larval moulting, feeding, tissue penetration and migration (Mladineo et al., 2023 ; Palomba, Rughetti, et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also propose further studies on extracellular vesicles, as recent studies have enabled their fluorescent labelling in Anisakis , facilitating work with them [ 33 ], which is very important due to their potential as a mechanism of communication and interaction between parasite and host. Their contents include DNA, proteins, and non-coding RNAs, such as microRNAs (already in evidence in A. pegreffii L3 [ 34 ]), which play relevant roles in all aspects of cellular life through post-transcriptional gene regulation, potentially promoting the degradation and/or translational repression of target messenger RNAs [ 35 ]. Thus, parasites could use their extracellular vesicles to potentially regulate host genes that, among other possible functions, could regulate host immune and inflammatory responses [ 32 ].…”
mentioning
confidence: 99%